[tex]a)\\\\ 2\frac{1}{2}:5 - \frac{1}{3}= \frac{\not{5}^1}{2}*\frac{1}{\not{5}^1} - \frac{1}{3}=\frac{1}{2}-\frac{1}{3}=\frac{3}{6}-\frac{2}{6}=\frac{1}{6}\\\\b)\\\\(3\frac{1}{3} + \frac{5}{9}):7=( \frac{10}{3} + \frac{5}{9})*\frac{1}{7}=( \frac{30}{9} + \frac{5}{9})*\frac{1}{7}=\frac{\not{35}^5}{9}*\frac{1}{\not{7}^1}=\frac{5 }{9}\\\\c)\\\\(1 \frac{4}{7} - \frac{4}{3}):10=( \frac{11}{7} - \frac{4}{3})*\frac{1}{10}=( \frac{33}{21} - \frac{28}{21})*\frac{1}{10}=\frac{\not{5}^1}{21} *\frac{1}{\not{10}^2}=\frac{1}{42}[/tex]
[tex]d)\\\\ (5\frac{1}{5 }-2\frac{3}{4}):2^2=( \frac{26}{5 }- \frac{11}{4}):4= ( \frac{104}{20}- \frac{55}{20}) *\frac{1}{4}=\frac{49}{20} *\frac{1}{4} =\frac{49}{80}\\\\e)\\\\((2\frac{1}{2})^2-\frac{3}{4}):11=(( \frac{5}{2})^2-\frac{3}{4})*\frac{1}{11}=( \frac{25}{4} -\frac{3}{4})*\frac{1}{11} =\frac{22}{4}*\frac{1}{11}=\frac{\not{11}^1}{2}*\frac{1}{\not{11}^1}=\frac{1}{2}\\\\f)\\\\(2\frac{1}{3})^2:7-\frac{2}{3}=( \frac{7}{3})^2* \frac{1}{7}-\frac{2}{3}= \frac{\not{49}^7}{9} * \frac{1}{\not{7}^1}-\frac{2}{3}=\frac{7}{9}-\frac{6}{9}=\frac{1}{9}[/tex]